The Effect of the Video "Young Smart Without Drugs" Is Effective In Increasing Adolescents' Knowledge About Drugs: Pengaruh Video “Muda Cerdas Tanpa Napza” Efektif Meningkatkan Pengetahuan Remaja Tentang Napza - Septalia Mumpuniati; Iskandar Arfan; Linda Suwarni (Indonesian Journal of Administration and Health Research (IJAHR), 2024)
Background: The prevalence of drug abuse in 2019 was 0.80% of the total population of West Kalimantan province. Students, especially at the high school/vocational level, are at the top of the drug abuse list. Objective: This study aims to determine the effectiveness of education through animated video media "Young Smart Without Drugs" on adolescents' knowledge about drugs in class XI at SMK Negeri 4 Pontianak. Methods: This research is a pre-experimental research with one group pretest and posttest design. The population in this study were all grade XI students at SMK Negeri 4 Pontianak in the 2021/2022 school year, totaling 592 students. Results: There is a significant difference in knowledge before the intervention (4.80) and after the intervention (9.73) of the animated video education "Young Smart Without Drugs".  The test results obtained a p value of 0.000 <0.05.  Conclusion: Animated video media "Young Smart Without Drugs" can be an alternative media used in education to increase adolescents' knowledge in preventing drug abuse.